Case Report: PD-1 Blockade Combined Autologous Hematopoietic Stem Cell Transplantation With Modified BEAM Regimen Containing High-Dose Cytarabine to Treat R/R Hodgkin's Lymphoma - Wang, Xiaoqi; Cassady, Kaniel; Zou, Zhongmin; Zhang, Xi; Feng, Yimei (Frontiers in Medicine, 2021)
The emergence of new drugs has provided additional options in the treatment of relapsed and refractory (R/R) Hodgkin's Lymphoma (HL). However, use of autologous stem cell transplantation (ASCT) has not been completely replaced in this setting. The use of anti-PD1 antibody bridging to ASCT and as maintenance after transplantation is novel approach in HL treatment. In this case, we report that PD1 mAb plus ASCT with modified BEAM containing high dose of cytarabine to treat R/R HL may represent a promising regimen in this difficult-to-treat setting.